Fertilitiy Characteristics of Cattle Production in Enterprises Belonging to Cattle Breeding Association in Devrekani - Tüzemen, Naci (Zootekni Federasyonu (ZF), 2020)
In this study, some reproductive performance characteristics of cattle raised in two enterprises belonging to Kastamonu Devrekani provincial breeding cattle breeders association were investigated. The mean value of the smallest squares of the first calving age, service period and calving interval of Holstein cattle was 26,931 ± 0,125 months; 174,838 ± 5,335 days; 440,519 ± 3,773 days respectively. As a result of the analysis of variance, the effect of age and age on the first calving age of Holstein cows grown in two different farm in the province of Devrekani is very significant (P<0.01) and seasonal effect is insignificant. In the service period, the effect of the age of the mother was significant (P<0.05), the effect of the season was very significant (P<0.01) and the effect of the enterprise was negligible. Enterprise and age of cow, very important effect on calving interval (P<0.01), while the impact of the seasonal effect was not significant.Reproductive performance and effective factors were found to be positive and significant (P<0.01). İn terms of the correlation coefficients calculated between birth season, cow age, first calving age, service period. However, there were negative and very significant correlations (P<0.01) between the fertility characteristics (excluding service period) and the fertility characteristics that were considered by the enterprise factor.

Bu çalışmada, Kastamonu ili Devrekani ilçesi damızlık sığır yetiştiricileri birliğine üye iki işletmede yetiştirilen sığırların bazı döl verim özellikleri araştırılmıştır. Siyah Alaca sığırlarının ilk buzağılama yaşı, servis periyodu ve buzağılama aralığına ait en küçük kareler ortalama değeri sırasıyla, 26,931±0,125 ay; 174,838±5,335 gün; 440,519±3,773 gün olarak belirlenmiştir. Yapılan varyans analizi sonucunda Devrekani ilçesinde iki ayrı işletmede yetiştirilen Siyah Alaca sığırlarının ilk buzağılama yaşına işletme ve ana yaşının etkisi çok önemli (P<0.01) mevsimin etkisi ise önemsizdir. Servis periyoduna ana yaşının etkisi önemli (P<0.05), mevsimin etkisi çok önemli (P<0.01), işletme etkisi ise önemsiz olmuştur. Buzağılama aralığına işletme ve ana yaşının etkisi çok önemli (P<0.01), mevsimin etkisi etkisi ise önemsiz bulunmuştur. Devrekani’de iki ayrı işletmenin döl verim özellikleri ve buna etkili faktörler, doğum mevsimi, ana yaşı, ilk buzağılama yaşı, servis periyodu, buzağılama aralığı arasında hesaplanan korelasyon katsayıları ve önemlilik durumu bakımından bulunan değerler genellikle pozitif ve çok önemlidir (P<0.01). Ancak işletme faktörü ile ele alınan döl verimi özellikleri (servis peryodu hariç) arasında negatif ve çok önemli (P<0.01) korelasyonlar bulunmuştur.
Keywords: Dairy cattle; Fertility; Calving interval; Breeders associations; Devrekâni; Hayvansal Üretim (Diğer); Zootechny (Other); Süt Sığırı; Döl Verimi; Buzağılama Aralığı; Damızlık Birliği; Devrekâni; 2. Zero hunger